2013
DOI: 10.1016/j.molmet.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl ester transfer protein protects against insulin resistance in obese female mice

Abstract: Cholesteryl ester transfer protein (CETP) shuttles lipids between lipoproteins, culminating in cholesteryl ester delivery to liver and increased secretion of cholesterol as bile. Since gut bile acids promote insulin sensitivity, we aimed to define if CETP improves insulin sensitivity with high-fat feeding. CETP and nontransgenic mice of both sexes became obese. Female but not male CETP mice had increased ileal bile acid levels versus nontransgenic littermates. CETP expression protected female mice from insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 45 publications
3
40
3
Order By: Relevance
“…Interestingly, CETP expression also results in a significant increase in fecal bile acids in vehicle treated animals (Supplemental Figure VIID). Increased bile acid synthesis has previously been reported in CETP transgenic mice 57, 58 . Little or no difference was observed in hepatic 3 H-cholesterol levels among the groups (data not shown).…”
Section: Resultsmentioning
confidence: 63%
“…Interestingly, CETP expression also results in a significant increase in fecal bile acids in vehicle treated animals (Supplemental Figure VIID). Increased bile acid synthesis has previously been reported in CETP transgenic mice 57, 58 . Little or no difference was observed in hepatic 3 H-cholesterol levels among the groups (data not shown).…”
Section: Resultsmentioning
confidence: 63%
“…Previously, CETP was shown to improve HDL function in women, but not men (15). Additionally, we have shown that transgenic expression of CETP protected against insulin resistance in females (16), recapitulating how estrogen increases insulin sensitivity in women. This suggests that CETP may facilitate estrogen-specific functions.…”
Section: Estrogen Treatment Raises Tg Production In Cetp Femalesmentioning
confidence: 57%
“…Because liver ER was not required to raise TG production in response to estrogen treatment in CETP mice, we sought to determine additional factors required for this effect in CETP mice. Previously, we showed that CETP expression enhanced bile acid signaling to the nuclear receptor SHP in females (16). SHP regulates a number of metabolic pathways, including VLDL-TG production (26) and estrogen signaling (27,28).…”
Section: Cetp Requires Liver Shp To Increase Tg Production With Estromentioning
confidence: 99%
“…Our analysis of CETP expression in several databases across cell line, BC tissue and patient gene expression data also provides evidence for the implication of CETP in BC as it was found commonly overexpressed in BC cases, correlated with poor relapse free and overall survival and a significant probability of poor long-term survival for ER+ BC patients. These observations may be crucial in light of the evidence that CETP : is elevated in BC; increases cholesterol uptake in BC cells; mediates the transfer of free cholesterol between lipoproteins and membranes; shuttles estradiol (E2) between HDL and LDL; and augments estradiol delivery to tissues, potentially enhancing estrogen signalling [24]. Furthermore, AP significantly decreased estrogen receptor– 1 (ESR-1) and elevated the CETP inhibitor APOF gene expression which further adds another level of regulation mediated by the therapeutic small molecule (AP) in the CETP pathway (Figure S6F and G).…”
Section: Discussionmentioning
confidence: 99%
“…The cholesteryl ester transfer protein (CETP) shuttles cholesteryl esters (CEs) and triglycerides between HDL and LDL to maintain cholesterol homeostasis both intracellularly and extracellularly [22]. CETP has been shown to prevent development of atherosclerotic lesions in ovariectomized hypercholesterolemic mice [23],and a link between CETP and estrogen has also been proposed [24]. Furthermore, CETP-deficient cells have been reported to have lower cholesterol content as CETP deficiency impeded CE transport from its site of synthesis to the storage droplet thereby reducing CE hydrolysis [25].…”
Section: Introductionmentioning
confidence: 99%